85.5k views
1 vote
Verify (a+b+c)^2=a^2+b^2+c^2+2ab+2bc+2ca
With the observation answer

User Alpian
by
4.9k points

1 Answer

6 votes

Answer:

see explanation

Explanation:

(a + b + c)² = (a + b + c)(a + b + c)

Each term in the second factor is multiplied by each term in the firs factor, that is

a(a + b + c) + b(a + b + c) + c(a + b + c) ← distribute all 3 parenthesis

= a² + ab + ac + ab + b² + bc + ac + bc + c² ← collect like terms

= a² + b² + c² + 2ab + 2bc + 2ac

User Endyd
by
5.1k points